1998
DOI: 10.1007/s100510050324
|View full text |Cite
|
Sign up to set email alerts
|

Monolayers of diblock copolymer at the air-water interface: the attractive monomer-surface case

Abstract: We have studied both experimentally and theoretically the surface pressure isotherms of copolymers of polystyrene-polyethyleneoxide (PS-PEO) at the air-water interface. The SCMF (single chain mean-field) theory provides a very good agreement with the experiments for the entire range of surface densities and shows that the adsorption energy per PEO monomer at the air-water interface is about one kBT . In addition, the chain density profile has been calculated for a variety of surface densities, from the dilute … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

31
197
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(230 citation statements)
references
References 24 publications
31
197
2
Order By: Relevance
“…Bijsterbosch and coworkers 19 estimated an effective adsorption energy of 0.4 k B T per monomer using scaling estimates of the surface density of EO monomers. Faure and co-workers 21 found optimal agreement between their measured isotherms and ones obtained from single chain mean-field calculations when their adsorption energy parameter was chosen to be about 1 k B T per monomer. Given the smooth transition to the pseudoplateau in the experimental data (as opposed to a sharp transition in the SCMF predictions), it is difficult to estimate the onset of segment desorption with high accuracy.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bijsterbosch and coworkers 19 estimated an effective adsorption energy of 0.4 k B T per monomer using scaling estimates of the surface density of EO monomers. Faure and co-workers 21 found optimal agreement between their measured isotherms and ones obtained from single chain mean-field calculations when their adsorption energy parameter was chosen to be about 1 k B T per monomer. Given the smooth transition to the pseudoplateau in the experimental data (as opposed to a sharp transition in the SCMF predictions), it is difficult to estimate the onset of segment desorption with high accuracy.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…19,21 The appearance of a pseudoplateau at a surface pressure of approximately 10 mN/m is linked to the onset of solubilization of PEO segments and the transition between a fully adsorbed copolymer layer to a configuration where the PS blocks stay anchored at the interface and PEO chains form a brush in the water subphase. Bijsterbosch and coworkers 19 estimated an effective adsorption energy of 0.4 k B T per monomer using scaling estimates of the surface density of EO monomers.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Poly(styrene) block of the copolymer exists in a collapsed state because both water (or K 2 SO 4 subphases) is a nonsolvent for PS. Fig 2 shows that increasing K 2 SO 4 concentration makes the solvent quality for PEO incrementally worse, which, in turn, results in more PEO segments attached to the interface and in higher surface pressures [19,20].…”
Section: Pressure -Area Isotherms Of Ps-b-peomentioning
confidence: 99%
“…The conformation of PEO chains at each subphase condition can be deduced from the π-A isotherm. At low surface pressures (π < 5 mN/m) PEO chains are known to be adsorbed to the air-water interface in so-called "pancake" configuration [11,19,20]. Poly(styrene) block of the copolymer exists in a collapsed state because both water (or K 2 SO 4 subphases) is a nonsolvent for PS.…”
Section: Pressure -Area Isotherms Of Ps-b-peomentioning
confidence: 99%
“…Pioneering work in this field has been made by Szleifer and coworkers, which in a series of papers [97][98][99][100][114][115][116] systematically addressed how the thermodynamics and the kinetics of protein adsorption are affected by the presence of polymer brushes. Considering equilibrium properties, it was found that a higher grafting density better prevents protein adsorption due to steric repulsion and the competition between monomers and polymer to adsorb on the surface, a result also suggested in an earlier work of de Gennes.…”
Section: Predicting and Controlling Protein Adsorptionmentioning
confidence: 99%